1993
DOI: 10.1111/j.1365-3083.1993.tb03319.x
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Lymphocyte and Monocyte Functional Activity by Polymorphonuclear Neutrophils in HIV Infection

Abstract: The aim of this study was to determine whether polymorphonuclear neutrophils (PMN) can modify the immune response in HIV cases. Supernatants of PMN (PMNS) from 33 HIV-infected patients (16 with lymphoadenopathy syndrome, 17 with AIDS-related complex) were tested for their influence on the functional activity of lymphocytes and monocytes from 6 healthy donors. PMNS from another 6 healthy donors comprised a control group. It was found that PMNS from HIV-infected patients, but not from healthy donors, induced sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…We cannot exclude the possibility that a switch in the ratio of T cells to neutrophils, rather then an absolute increase in the number of neutrophils, could be responsible for the increase in the level of arginase activity; however, when we exclude the number of cells as a factor in the calculation of the levels of arginase activity, our results clearly show that the levels of arginase activity are statistically significantly higher in HIV-seropositive patients with low CD4 + T cell counts, compared with HIV-seropositive patients with high CD4 + T cell counts. An impairment of T cell functions by neutrophils has already been demonstrated in HIV-seropositive patients [34].…”
Section: Discussionmentioning
confidence: 98%
“…We cannot exclude the possibility that a switch in the ratio of T cells to neutrophils, rather then an absolute increase in the number of neutrophils, could be responsible for the increase in the level of arginase activity; however, when we exclude the number of cells as a factor in the calculation of the levels of arginase activity, our results clearly show that the levels of arginase activity are statistically significantly higher in HIV-seropositive patients with low CD4 + T cell counts, compared with HIV-seropositive patients with high CD4 + T cell counts. An impairment of T cell functions by neutrophils has already been demonstrated in HIV-seropositive patients [34].…”
Section: Discussionmentioning
confidence: 98%
“…Neutrophils also regulate NK cell functions (Seaman et al, 1982;Dallegri et al, 1985;Shau and Kim, 1988;Shau and Golub, 1989;Gabrilovich et al, 1993;Sporri et al, 2008), maturation ( Jaeger et al, 2012), and homeostasis ( Jaeger et al, 2012). Recent evidences revealed that NK cells were less responsive, more proliferative, and less mature in patients suffering from SCN ( Jaeger et al, 2012).…”
Section: Crosstalk Between Neutrophils and Nk Cellsmentioning
confidence: 99%
“…In both studies, the neutrophil-mediated, suppressive action was reversed by catalase (a H 2 O 2 -detoxifying enzyme) but not SOD (which instead, converts O 2 to H 2 O 2 ) [39,40], indicating that it was dependent specifically on H 2 O 2 . Since then, it has been confirmed consistently, using PBMCs/PBLs or purified NK cells, that granulocyte-derived ROS have inhibitory effects on several NK cell effector functions, ranging from NK-dependent cytotoxic activities to NK survival or the expression of NCRs [35][36][37][38][41][42][43][44]. Interestingly, 3 studies [37,38,44] have identified NK subset-specific differences further in terms of sensitivity to neutrophil-derived ROS.…”
Section: Modulation Of Nk Cell Effector Functions By Neutrophils: Rolmentioning
confidence: 99%